Women Under-Representation in Politics, Factors Responsible: A Case of Yobe State - Abubakar , Yakaka (Kashere Journal of Politics and International Relations, 2025)
Wqmen are under-represented in political institutions globally. In Nigeria and Yobe State in particular, under-representation of women is glaring at the executive, legislative and judicial arms of government. Anchored on the theory of empowerment, this research evaluates women’s under-representation in politics: factors responsible for the predicament in Yobe State. The objective of the study is to identify the factors responsible for women’s under-representation in Yobe; explore the consequences of women’s under-representation in politics and develop strategies that will increase participation of women in decision making process. A qualitative research design was adopted and an In-depth interview method was used to elicit data from 20 Key Information Informants across Yobe State particularly from ministry of women affairs and women in business. The study found that under-representation of women in Yobe State is caused by patriarchy, coercion, cultural/religious barriers, stigma, godfatherism, lack of interest and intimidation/threats. It also discovered that the consequences of women’s under-representation in politics include inequality, poverty, loss of voice, anti-women policies and erosion of democratic values and principles. The study concludes that women are totally not represented in Yobe State politics, and recommended strategies to turn the tide, including combating cultural/ religious barriers, mentorship, adoption of quota system, increased advocacy, direct primaries and a policy of free nomination forms for female contestants. Findings from this study are a reference point to policy makers, academics and non-governmental organizations, women themselves and other stake holders that are relevant to the field.